2003
DOI: 10.1136/gut.52.5.706
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the BRAF gene in cholangiocarcinoma but not in hepatocellular carcinoma

Abstract: Our data indicate that BRAF gene mutations are a relatively common event in CC but not in HCC. Disruption of the Raf/MEK/ERK (MAPK) kinase pathway, either by RAS or BRAF mutation, was detected in approximately 62% of all CC and is therefore one of the most frequent defects in cholangiocellular carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
238
5
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(259 citation statements)
references
References 20 publications
7
238
5
9
Order By: Relevance
“…Our findings are in line with recently published smaller series detecting BRAF mutations in 1% to 4% of evaluated cases. [26][27][28] We cannot confirm the exceedingly high mutation rates detected in early BRAF studies of European cohorts, 29,30 and conclude that the previously assumed regional difference in the genetics of biliary tract cancer in Europe versus the Americas is not existent. 2 Our data further demonstrate that BRAF mutations are restricted to intrahepatic cholangiocarcinomas and account for 3% in this subgroup.…”
Section: Discussionmentioning
confidence: 56%
“…Our findings are in line with recently published smaller series detecting BRAF mutations in 1% to 4% of evaluated cases. [26][27][28] We cannot confirm the exceedingly high mutation rates detected in early BRAF studies of European cohorts, 29,30 and conclude that the previously assumed regional difference in the genetics of biliary tract cancer in Europe versus the Americas is not existent. 2 Our data further demonstrate that BRAF mutations are restricted to intrahepatic cholangiocarcinomas and account for 3% in this subgroup.…”
Section: Discussionmentioning
confidence: 56%
“…After microdissection, 22,23 methylation-specific PCR (MSP) was used to investigate the methylation status of the promoter region of the BLU, RASSF1A and SEMA3B genes. Microdissection was performed as described previously.…”
Section: Methylation Analysismentioning
confidence: 99%
“…Microdissection was performed as described previously. 22,23 After an initial bisulfite treatment to modify the DNA, PCR was performed to distinguish methylated from unmethylated DNA as described by Herman et al 24 Briefly, 2 mg of genomic DNA was denatured with 0.3 M NaOH; 10 mM hydroquinone and 3 M sodium bisulfite were added and incubated for 16 hr at 508C. Afterward, modified DNA was purified using the Wizard DNA purification resin (Promega, Madison, WI) followed by desulfonating in 0.3 M NaOH and subsequent ethanol precipitation and resuspension in 30-50 ml water.…”
Section: Methylation Analysismentioning
confidence: 99%
“…The MAPK/ERK pathway is essential and critical for hepatic progenitor cell proliferation [41]. A report showed that disruption of the RAF/ MEK/MAPK pathway by a RAS or BRAF mutation was detected in more than 60 % of cholangiocarcinomas, indicating that these pathways are important in cholangiocarcinoma carcinogenesis [57]. Interestingly, it is a relatively specific event in cholangiocarcinoma rather than in hepatocellular carcinoma [57].…”
Section: Raf/mek/mapk Signaling Pathwaymentioning
confidence: 99%